Penerapan Model Pembelajaran Beyond Centers And Circle Time (Bcct) Dalam Perkembangan Aspek Kognitif Anak Usia Dini di TKIT Al Husna - Andriani, Linda; Maulana, Redi Awal; Elnawati, Elnawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of the application of the Beyond Centers and Circle Time (BCCT) learning model in improving the development of cognitive aspects of early childhood at TKIT Al Husna, Nyalindung District, Sukabumi Regency. The method used is Classroom Action Research (PTK) with a spiral model from Kemmis and McTaggart consisting of four stages: planning, action, observation, and reflection. The subjects of this study were 13 children aged 5-6 years in the even semester of the 2024/2025 school year. Learning activities are carried out in the beam center as the main media to stimulate the ability to think logically, recognize the concepts of shape, size, and pattern. Data collection techniques were carried out through observation and documentation, with instruments in the form of child cognitive development assessment sheets. The results showed a significant increase in cognitive aspects. In the pre-action, as many as 8 children (62%) were in the Underdeveloped category (BB). After the application of BCCT in Cycle I, the number of children in the BB category decreased to 2 children (15.38%), and increased to 10 children (76.92%) who reached the Very Well Developed category (BSB) in Cycle II. Thus, the application of the BCCT model is proven to be effective in stimulating the cognitive development of early childhood at TKIT Al Husna. Keywords: Beyond Centers and Circle Time, BCCT, cognitive aspects, early childhood, beam center, PAUD